2009
DOI: 10.1038/ismej.2009.105
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal ammonia oxidizers and nirS-type denitrifiers dominate sediment nitrifying and denitrifying populations in a subtropical macrotidal estuary

Abstract: Nitrification and denitrification are key steps in nitrogen (N) cycling. The coupling of these processes, which affects the flow of N in ecosystems, requires close interaction of nitrifying and denitrifying microorganisms, both spatially and temporally. The diversity, temporal and spatial variations in the microbial communities affecting these processes was examined, in relation to N cycling, across 12 sites in the Fitzroy river estuary, which is a turbid subtropical estuary in central Queensland. The estuary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
124
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 50 publications
23
124
3
1
Order By: Relevance
“…Immediately following thawing, sediment samples were homogenised using a spatula, and DNA was extracted and quantified as previously described (Abell et al 2010). The amoA, nirS and 16S rRNA genes were amplified from DNA extractions using the primers and cycling conditions described in Table S1 in the Supplement at www.…”
Section: Molecular Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Immediately following thawing, sediment samples were homogenised using a spatula, and DNA was extracted and quantified as previously described (Abell et al 2010). The amoA, nirS and 16S rRNA genes were amplified from DNA extractions using the primers and cycling conditions described in Table S1 in the Supplement at www.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Standards for qPCR were generated by serial dilutions of known copies of PCR fragments of the respective functional gene generated using M13 PCR from clones generated during the present and previous studies (data not shown). Samples were assayed as previously described (Abell et al 2010) to ensure that there was no significant effect of PCR inhibition on the qPCR data.…”
Section: Molecular Analysismentioning
confidence: 99%
See 3 more Smart Citations